Spatial Variability of Rice Grain Arsenic in Confined and Unconfined Basins of Ganges River Floodplain Soils of Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
Arsenic (As) accumulates in rice grain from contaminated irrigation water and soils may vary with the land types and water receiving basins. Two confined and one unconfined basins comprised of different land types in the As contaminated Ganges River Floodplain soils of Faridpur district of Bangladesh were selected to assess the contribution of different land types on spatial distribution of As uptake by rice grain. Sites in Faridpur Sadar and Madhukhali upazilas were confined basins, while a third site in Boalmari upazila was an unconfined basin connected to a river. Each site consisted of a mosaic of between 16-31 shallow tube well (STW) irrigation command areas with water As concentrations ranging from about 20 to 170 ?g-l in Faridpur and Boalmari sites and 20-110 ?g-l in Madhukhali site. Soil arsenic concentrations ranged from about 4-42, 5-31 and 5-29 mg kg-1 in Madhukhali, Faridpur Sadar and Boalmari, respectively, while the resultant rice grain As were 0.22 - 0.69, 0.095 0.751 and 0.030 0.92 mg kg-1, respectively. Arsenic concentrations in rice grain of different sites were in the order of Madhukhal>Faridpur Sadar>Boalmari basin. Arsenic accumulated high in the confined basins because of its less mobilization while more mobilization and loss of As in the open unconfined basin was obvious which materialized in the rice grain arsenic of the corresponding study sites.J. Environ. Sci. & Natural Resources, 8(2): 51-55 2015